Appearance of mycovirus‐like double‐stranded RNAs in the white root rot fungus, Rosellinia necatrix, in an apple orchard. Issue 1 (14th August 2012) - Yaegashi, Hajime; Nakamura, Hitoshi; Sawahata, Takuo; Sasaki, Atsuko; Iwanami, Yasuhiko; Ito, Tsutae; Kanematsu, Satoko
Abstract In general, mycoviruses are transmitted through hyphal anastomosis between vegetatively compatible strains of the same fungi, and their entire intracellular life cycle within host fungi limits transmission to separate species and even to incompatible strains belonging to the same species. Based on field observations of the white root rot fungus, Rosellinia necatrix, we found two interesting phenomena concerning mycovirus epidemiology. Specifically, apple trees in an orchard were inoculated with one or two R. necatrix strains that belonged to different mycelial compatibility groups (MCGs), strains W563 (virus‐free, MCG139) and NW10 (carrying a mycovirus‐like double‐stranded (ds) RNA element (N10), MCG442). Forty‐two sub‐isolates of R. necatrix, which were retrieved 2–3 years later, were all genetically identical to W563 or NW10: however, 22 of the sub‐isolates contained novel dsRNAs. Six novel dsRNAs (S1‐S6) were isolated: S1 was a new victorivirus; S2, S3, and S4 were new partitiviruses; and S5 and S6 were novel viruses that could not be assigned to any known mycovirus family. N10 dsRNA was detected in three W563 sub‐isolates. These findings indicated that novel mycoviruses, from an unknown source, were infecting strains W563 and NW10 of R. necatrix in the soil, and that N10 dsRNA was being transmitted between incompatible strains, NW10 to W563.